A retrospective comparative analysis of elderly and younger patients undergoing pulmonary resection for stage I non-small cell lung cancer. Issue 1 (December 2015) - Park, Byungjoon; Lee, Genehee; Kim, Hong; Choi, Yong; Zo, Jae; Shim, Young; Kim, Jhingook
Abstract Background Age has been a critical predictor for immediate postoperative and long-term results after the pulmonary resection for lung cancer. In this study, we evaluated and compared surgical outcome of stage I non-small cell lung cancer and associated predictive factors between elderly and younger groups. Methods Short- and long-term outcomes of elderly group (≥70 years) who were surgically treated and pathologically diagnosed as stage I non-small cell lung cancer from 2004 to 2010 were compared to the results of younger group (<70 years). Results Total of 1340 patients were included in this study, and the patients were divided into the elderly group (n = 285) and the younger group (n = 1055). The proportions of squamous cell carcinoma (36.8 vs. 20.0 %, p < 0.001) and stage IB cancer (58.3 vs. 40.6 %, p < 0.001) were significantly higher in the elderly group than the younger group. The 30-day and 90-day mortalities were significantly higher in the elderly group (1.8 vs. 0%;p = 0.014, 3.9 vs. 0.5 %;p < 0.001, respectively). The elderly patients also had significantly worse long-term outcomes than the younger group (5-year overall survival rate, 69.0 vs. 91.1 %;p < 0.001, 5-year disease-free survival rate, 53.3 vs. 80.2 %;p < 0.001). Decreased diffusion capacity less than 70 % was an important predictive factor for short- and long-term outcomes in both the younger and the elderly group. Conclusions Elderly patients with low diffusion capacity are at risk for significantly worse outcome, indicating that patient selection should include assessment of pulmonary function, including diffusion capacity.